The Meme as a Form of Postmodern Text in Modern Russian Communication (Uzbekistan Open Conference, 2025)
This article examines the phenomenon of the internet meme as a specific form of postmodern text in the context of modern Russian communication. It analyzes the key characteristics of memes—intertextuality, irony, deconstruction, and hybridity—which make them an important tool for cultural transformation and social interaction in the digital environment. Based on the theoretical approaches of postmodernism (J. Baudrillard, J.-F. Lyotard) and empirical examples from the Russian internet (such as “Preved Medved,” “Zhdun,” and political memes), the article reveals the role of memes in shaping collective consciousness, propaganda, and everyday communication. The study emphasizes that memes reflect the postmodern relativization of values and contribute to the evolution of language in the era of digital networks. The article also offers recommendations for further research on memes as a cultural phenomenon.